The use of chemical stabilisers in labour intensive road construction - Van Steenderen, Willem Pieter Cornelis (My University, 1995)
Until recently use of ionic chemical soil stabilisers seemed hit or miss. The paper by paige-Green and Bennett explains that the stabilisers work only on soils containing reactive clays. The author's findings confirm this conclusion. It was shown that a CBR test, which can be done in any road soils laboratory, can be used to measure the chanqe in strength caused by the treatment of the soil with a chosen ionic stabiliser. South Africa is faced with a serious unemployment problem. The World Bank and the International Labour Organisation have shown that employment in construction can be significantly increased by the use of labour instead of machinery. Field trials showed that ionic stabilisers can readily be applied labour intensively. These stabilisers could imprpve marginal materials to road-building standard and this could further reduce the dependence on machinery by reducing the need to transport quantities of high quality gravel.
A project report submitted to the Faculty of Engineering, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Science in Engineering.
Keywords: Soil conditioners; Soil stabilization; Public service employment -- South Africa